Electrospinning-Driven Advancements in Lithium-Ion Battery and Fuel Cell Technologies: From Nanofiber Fabrication to Application - Yang Jiacheng (MATEC Web of Conferences)
The transition from fossil fuels to sustainable energy storage systems necessitates addressing critical limitations in conventional battery and fuel cell technologies. Electrospinning, a scalable nanofiber fabrication technique, has emerged as a revolutionary tool for optimizing electrode and proton exchange membrane (PEM) performance. This review systematically explores the electrospinning process, emphasizing its ability to engineer micro-/nanoscale architectures with tailored porosity, conductivity, and mechanical properties. Key applications include the production of high- surface-area nanofibers for lithium-ion (LIBs) and sodium-ion batteries, as well as PEMs with enhanced proton conductivity and gas selectivity. By integrating conductive additives (e.g., carbon nanotubes) and functional groups (e.g., -SO₃H), electrospun materials achieve superior energy density, cycling stability, and cost-effectiveness. Furthermore, advanced characterization techniques (PXRD, SEM, TGA) validate structural and thermal advantages over conventional materials. This study highlights electrospinning’s pivotal role in advancing clean energy technologies and provides insights for future research directions, including high-temperature- resistant polymers and real-time process monitoring.